ANALISIS HUKUM ISLAM PERMAINAN HIGGS DOMINO ISLAND DI KALANGAN MAHASISWA IAIN PONTIANAK - Rizka Triandryani; Syahbudi Syahbudi; Ishar Pulungan (Al-Aqad, 2024)
This research aims to find out the factors that encourage the Higgs Domino Island (HDI) game to be popular among IAIN students and to find out the views of Islamic Law related to chip buying and selling transactions. This research uses qualitative research methods with the type of field research and normative sociological approach. The data source uses primary data obtained from interviews with IAIN Pontianak students, while secondary data is obtained from various sources, namely book journals and the internet that are relevant to the focus of the research. Data collection techniques were obtained by conducting observations, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. Then the data is checked for validity by triangulating sources, triangulating data. This research shows that the practice of buying and selling Higgs Domino Island game chips starts from various social media such as Facebook, WA, and various other applications but buyers and sellers can also trade their chips in a direct way such as fellow friends, buyers easily buy their chips. Buying and selling in the online game Higgs Domino Island is the object that is traded which is not materially handed over in the hand, but the object can be utilized and also transferred. The transaction of buying and selling HDI online game chips Ijab and Qabul is clear. Because it is clear that the seller sells something with awareness, and the buyer also buys something that is sold. However, from the point of view of the terms and conditions, the sale and purchase of chips in HDI online games contains elements of maysir, so it is not in accordance with Islamic Law.